Implementation of Shopeee E-Commerce Business Ethics Based on Maqashid Al-Syari'ah: Abu Ishaq Asy-Syathibi's Thoughts - Rizma Denytasari; Rokhmat Subagiyo; M. Aqim Adlan (Ravine Publisher, 2024)
The concept of Maqashid al-Syari’ah is very important to apply in the context of e-commerce business ethics because the concept of Maqashid al-Syari’ah directs business actions not only to focus on gaining profits but also to pay attention to sustainability and balance in important aspects of life. This research aims to examine the application of Shopee's e-commerce business ethics based on Maqashid al-Syari’ah according to Ash-Syathibi's thought. This research uses a qualitative approach using library research methods. Namely, data is collected by reviewing books and journals that are appropriate to this research, using the phenomenological method, namely data mining that discusses the specifics of this research, and also relies on critical analysis of primary and secondary sources related to this research. The results of this research are that business ethics based on Maqashid al-Syari’ah, according to Asy-Syathibi's thoughts, has a good impact on the sustainability of Shopee's business. By maintaining customer trust and implementing rules in accordance with Maqashid al-Syari’ah, Shopee is increasingly developing and being trusted by the public as a safe and trustworthy e-commerce platform. Apart from that, by maintaining a professional attitude and implementing five basic things that must be adhered to by all sellers, Shopee also provides a good example of running a business based on business ethics that are in accordance with Maqashid al-Syari’ah.